Pancasila Sebagai Teks Dialog Lintas Agama dalam Perspektif Hans-Georg Gadamer dan Hans Kung - Angel Christy Latuheru; Izak Y. M. Lattu; Tony Robert Tampake (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2020)
This article addresses Pancasila as a text of interfaith dialogue in Indonesian context. The plurality of Indonesian society bears religious uniqueness in social life together, while conflicts may take place between religious groups. Religious conflicts are caused by attitude of exclusivism, radicalism, fundamentalism of religions and political identity. Pancasila can hold the sense collectivity among Indonesian society to be united. This article employs Gadamer hermeneutic theory in viewing historical texts. History is not something that only happened in the past and is interrupted with the present contexts. The theory of global ethics-Hans Kung, also helps the importance of dialogue with the religious communities to create religious peace. The article concludes that plural and multicultural society must live together in a dialogue circle. Pancasila as the text of interfaith dialogue is always understood as dynamic, open and relevant in the development of religious society in Indonesia. As the national identity, Pancasila has more than one conception as the lighters and guide toward each dialogue strategy that has been undertaken. The values of Pancasilamaintain inclusive religious attitude, respect to human values, and become a solid foundation in maintaining the unity of religious people.